Engineering functional nanomaterials for biophotonics and nanomedicine applications - Ouyang, Qingling (2019)
To date, functional nanomaterials have been commonly synthesized and applied for various biomedical applications such as sensing, imaging, drug delivery, and tissue engineering due to their unique optical, electronic, and biocompatible property. In this Ph.D. work, different types of nanomaterials/nanodevices have been engineered, characterized, and studied for biophotonic sensing and nanodrug delivery therapy, namely, two-dimensional (2D) transition metal dichalcogenides (TMDCs), nanoporous polymers and triboelectric nanogenerator (TENG). The engineered solutions presented in the Thesis aims at addressing current limitations in healthcare diagnostics and therapeutics fields, particularly the low detection sensitivity of optical biosensors and the large footprint of stimuli-controlled drug delivery systems. The presentation of this Thesis work was divided into two parts. In the first part of Thesis, we studied the physical and optical property of a series of 2D TMDCs including molybdenum disulfide (MoS2), tungsten disulfide (WS2), molybdenum diselenide (MoSe2) and tungsten diselenide (WSe2), to develop and optimize next generation of plasmonic biosensors with high sensitivity for small molecules. The sensing performance is affected by types of 2D materials, thickness and incident wavelength. In theoretical studies, a monolayer WS2 based plasmonic biosensor was demonstrated to achieve a 200% increment in the detection sensitivity in the visible wavelength. In the experimental studies, the phase sensitivity of the WS2 sensing film reaches 15,000 deg/RIU in detecting low concentration analytes, which represents an enhancement of 151% over the conventional bare gold SPR sensing film. In addition, the enhanced SPR biosensor exhibits fast and accurate feedback in real-time monitoring of small molecules. In the second part of the work, we designed and studied the triboelectric nanogenerator (TENG) in creating a miniaturized, self-powered drug delivery device for transdermal patch application. TENG system can effectively convert various mechanical energies into electricity. It has many advantages such as the large output of power, low cost, simple fabrication, and high conversion efficiency. The designed transdermal patch mainly composed of an electric-responsive polymer and TENG. The drugs embedded in the polymer matrix were released upon receiving electric-stimuli from TENG. Such a mechanism can allow one to achieve precise control in programming the drug delivery profile by tailoring the appropriate TENG action time. The release rate can be tuned from ~ 0.05 to 0.25 μg/cm2. More importantly, the drug delivery efficiency in dermis was noted to improve by ~ 100% when compared with the absence of TENG triggered reaction. In conclusion, this Ph.D. work has generated reliable and emerging engineering solutions to overcome challenges we faced in the current healthcare diagnostic and therapeutic technology especially in the areas of optical plasmonic sensors and skin patch drug delivery devices. Such solutions can be further integrated into other sensing and drug delivery systems for personalized healthcare applications.